1999
DOI: 10.1007/s003940050063
|View full text |Cite
|
Sign up to set email alerts
|

Pollen-related food allergy: cloning and immunological analysis of isoforms and mutants of Mal d 1, the major apple allergen, and Bet v 1, the major birch pollen allergen

Abstract: We conclude that divergent allergenicity of apple strains mainly depends on different expression levels of the major allergen. Introduction of a proline residue in position 111 of Mal d 1 and in position 112 of Bet v 1 led to a drastic reduction of allergenicity of both the pollen and the food allergen, obviously also removing the cross-reactive epitope. Mutants with reduced IgE-reactivity but maintained T-cell reactivity may represent new candidates for a safer specific immunotherapy with reduced side-effects. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(145 citation statements)
references
References 20 publications
4
137
0
2
Order By: Relevance
“…However, results of tests in vivo with hypo-allergenic variants of food allergens have not been published so far. Furthermore, the results of this and previous studies [14,16] remind us that the IgE-binding epitopes are highly patient specific and site-directed mutagenesis can also enhance the IgE reactivity for at least a subgroup of patients, as observed for Pru av 1 Trp 45 ( Figure 3A) and Api g 1 Glu 44 ( Figure 3B). Hence, with allergens containing exclusively conformational IgE-binding epitopes, hypo-allergenic variants may be produced more easily by irreversibly preventing the folding process, as in the case of Pru av 1 Pro 112 , than by mutation of all assumed IgE-binding epitopes while maintaining the native tertiary structure.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, results of tests in vivo with hypo-allergenic variants of food allergens have not been published so far. Furthermore, the results of this and previous studies [14,16] remind us that the IgE-binding epitopes are highly patient specific and site-directed mutagenesis can also enhance the IgE reactivity for at least a subgroup of patients, as observed for Pru av 1 Trp 45 ( Figure 3A) and Api g 1 Glu 44 ( Figure 3B). Hence, with allergens containing exclusively conformational IgE-binding epitopes, hypo-allergenic variants may be produced more easily by irreversibly preventing the folding process, as in the case of Pru av 1 Pro 112 , than by mutation of all assumed IgE-binding epitopes while maintaining the native tertiary structure.…”
Section: Discussionsupporting
confidence: 74%
“…our previous observation that the mutation of Thr 10 to Pro does not affect the IgE-binding capacity of Pru av 1 [14], this suggests that the region on the adjacent first and seventh β-strands around Thr 10 and Ser 112 , which was suggested as a potential IgE-binding epitope of Bet v 1 [15], Mal d 1 [16] and Api g 1.0101 [12], does not constitute a clinically relevant cross-reactive IgE-binding epitope of Pru av 1.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…[10], [120], [121], [122] and [123] [124], [125], [126], [127], [128], [129] and [130] However, other studies at different shifting offsets, with different peptides sizes, or both revealed different sets of immunodominant sequential epitopes for the same allergens. [29], [124], [125], [126], [127], [130] and [131] Nevertheless, approaches to use these alleged immunodominant peptides for the risk assessment of life-threatening symptoms, as well as the prediction of persistence in food hypersensitivity, were apparently successful.…”
Section: Diagnosis Of Food Allergy With Synthetic Sequential Epitopesmentioning
confidence: 99%
“…Studies done by Son et al (1999) showed that allergenic differences between apple cultivars are mainly related to the expression levels of Mal d 1 and not to the presence of different isoformes, whereas Gao et al (2008) stated that differences in allergenicity are associated with the allelic composition of two specific genes (Mal d 1.04 and Mal d 1 1.06 A).…”
Section: Resultsmentioning
confidence: 99%